Analisis Leverage Ditinjau Dari Faktor Kebijakan Deviden Dan Ukuran Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Aminar Sutra Dewi; Desfriana Sari (JURNAL PUNDI, 2021)
Fast traslate Icon translate     Fast traslate Icon translate Manufacturing companies are companies that processing raw materials / goods into finished goods and goods that are ready to be consumed so that they require rather large. This study is intended to examine leverage analysis reviewed from devident policy factors and size of companies in manufacturing companies listed in indonesia stock exchange. The population is manufacturing companies at the end of the 2018 period, amounting to 163 companies. The sample collection technique using a purposive sampling method, 9 companies as samples. Data financial statements obtained from the official website of IDX. Used is panel data regression analysis with the help of E-Views 8 application. The initial test is to test the Chow-Test to decide whether the Pooled Least Square or Fixed Effect method is used; and the Hausman-Test to decide whether the Fixed Effect or Random Effect method can be used. The results showed that the dividend policy variable had a negative and significant effect on leverage, company size had a negative and not significant effect on leverage. Keywords: Devidend Policy, Firm Size, Leverage